Knowledge, attitude and practice on doping of Malaysian student athletes - Ming Chiang, Lim; Shamsuddin, Ahmad Fuad; Tuan Mahmood, Tuan Mazlelaa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of the study is to measure the knowledge, attitude, and practice of drugs use in sports among Malaysian student athletes. Methods: This was a cross-sectional, self-administered survey of student athletes studying in six universities and two sports schools in Malaysia. Athletes were approached at their schools or universities and were explained about the study. If they agreed to participate, they were asked to provide written informed consent and fill in the survey. Participation in the study was voluntary and no incentives were given. Results: Overall, 182 respondents were recruited for this study. Most of the respondents were male, age between 16 and 18 years old and had participated in international sports competition. The knowledge of the respondents on drugs in sports was found to be moderate with the median score of 11 per 18. The overall mean performance enhancement attitude scale scores, a measure of doping attitudes, for all respondents were 44.63 Â± 13.03 indicating they are having a negative attitude toward doping. Meanwhile, 12% of the respondents had been offered doping agents by any parties with 13.7% of them are using it for medical purpose while 4.4% of them had used it for other purposes. Conclusion: Young athletes should be better equipped with knowledge on the dangers of doping and have a firm stance against doping. Thus, specific educational package and special courses should be provided to address the knowledge gap observed among the athletes in this study apart from enhancing their attitude toward the importance of anti-doping.